Therapeutic versus Prophylactic Bemiparin in Hospitalized Patients with Nonsevere COVID-19 Pneumonia (BEMICOP Study): An Open-Label, Multicenter, Randomized, Controlled Trial - Marcos-Jubilar, María; Carmona-Torre, Francisco; Vidal, Rosa; Ruiz-Artacho, Pedro; Filella, David; Carbonell, Cristina; Jiménez-Yuste, Víctor; Schwartz, Juana; Llamas, Pilar; Alegre, Félix; Sádaba, Belén; Núñez-Córdoba, Jorge; Yuste, José R.; Fernández-García, Javier; Lecumberri, Ramón; for the BEMICOP Investigators (Thrombosis and Haemostasis, 2021)
Thromboprophylaxis with low molecular weight heparin in hospitalized patients with COVID-19 is mandatory, unless contraindicated. Given the links between inflammation and thrombosis, the use of higher doses of anticoagulants could improve outcomes. We conducted an open-label, multicenter, randomized, controlled trial in adult patients hospitalized with nonsevere COVID-19 pneumonia and elevated D-dimer. Patients were randomized to therapeutic-dose bemiparin (115 IU/kg daily) versus standard prophylaxis (bemiparin 3,500 IU daily), for 10 days. The primary efficacy outcome was a composite of death, intensive care unit admission, need of mechanical ventilation support, development of moderate/severe acute respiratory distress, and venous or arterial thrombosis within 10 days of enrollment. The primary safety outcome was major bleeding (International Society on Thrombosis and Haemostasis criteria). A prespecified interim analysis was performed when 40% of the planned study population was reached. From October 2020 to May 2021, 70 patients were randomized at 5 sites and 65 were included in the primary analysis; 32 patients allocated to therapeutic dose and 33 to standard prophylactic dose. The primary efficacy outcome occurred in 7 patients (22%) in the therapeutic-dose group and 6 patients (18%) in the prophylactic-dose (absolute risk difference 3.6% [95% confidence interval [CI], –16% –24%]; odds ratio 1.26 [95% CI, 0.37–4.26]; p = 0.95). Discharge in the first 10 days was possible in 66 and 79% of patients, respectively. No major bleeding event was registered. Therefore, in patients with COVID-19 hospitalized with nonsevere pneumonia but elevated D-dimer, the use of a short course of therapeutic-dose bemiparin does not appear to improve clinical outcomes compared with standard prophylactic doses. Trial Registration: ClinicalTrials.gov NCT04604327.
Keywords: COVID-19; low molecular weight heparin; outcomes; prophylactic therapeutic